2020
DOI: 10.1002/ps.6064
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of biocontrol agents against black‐foot and Petri diseases of grapevine

Abstract: BACKGROUND Black‐foot and Petri diseases are the main fungal diseases associated with young grapevine decline. Two field experiments were established to evaluate the preventive effect of two potential biocontrol agents (BCAs), that is Streptomyces sp. E1 + R4 and Pythium oligandrum Po37, and three BCA‐commercial products containing Trichoderma atroviride SC1, Trichoderma koningii TK7 and Pseudomonas fluorescens + Bacillus atrophaeus on fungal infection in grafted plants and plant growth parameters. RESULTS The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 60 publications
(148 reference statements)
0
56
0
Order By: Relevance
“…(Di Marco et al, 2004;Di Marco and Osti, 2007;Pertot et al, 2016;Berbegal et al, 2020) and Streptomyces spp. (Álvarez-Pérez et al, 2017;Martínez-Diz et al, 2021) and by other wound protection products (Díaz and Latorre, 2013) and foliar treatments to reduce the severity of leaf symptoms (Calzarano et al, 2014;Calzarano and Di Marco, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Di Marco et al, 2004;Di Marco and Osti, 2007;Pertot et al, 2016;Berbegal et al, 2020) and Streptomyces spp. (Álvarez-Pérez et al, 2017;Martínez-Diz et al, 2021) and by other wound protection products (Díaz and Latorre, 2013) and foliar treatments to reduce the severity of leaf symptoms (Calzarano et al, 2014;Calzarano and Di Marco, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In order to comply with the European legislation currently in force (Article 14 in European Directive 2009/128/EC), the implementation of integrated pest management (IPM) methods has become a priority objective in plant disease control worldwide. The efforts oriented towards the selection and/or development of rootstocks and varieties with certain levels of tolerance against different trunk mycoses have not been successful to date [11][12][13][14][15][16], and the use of strategies involving endophytic microorganisms as microbial antagonists (BCAs) obtains a certain degree of protection, but no single BCA application has been able to control GTDs at similar rates to those shown by chemical fungicides, which are now banned [17]. Hence, other alternative/complementary strategies have to be explored and improved, such as the application of substances of natural origin that are safe, effective and sustainable from an environmental point of view [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, on the contrary, studies carried out with some commercial Trichoderma-based bioproducts concluded that they did not show a good plant colonization ability under the selected conditions [28]. Similar controversial results have been reported for other non-fungal biological control agents, as in the case of Streptomyces [25,87]. These data show how important it is to continue studying the biotic and abiotic factors that affect the success of a good colonization as a key step to a good biocontrol activity.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, no positive effects were obtained in relation to the shoot and root weight in grapevine plants including a non-significant reduction in symptoms caused by black foot disease (caused by Dactylonectria torresensis, Dactylonectria macrodidyma, Ilyonectria liriodendri, and Dactylonectria alcacerensis) and Petri disease (caused by Cadophora luteo-olivacea, Phaeoacremonium minimum, and Phaeomoniella chlamydospora) and diseases in all BCAs assayed such as Trichoderma, Streptomyces, Pythium, Pseudomonas, and Bacillus spp. [25]. Different Trichoderma bio-formulated-based treatments applied on grapevine roots reduced their weight significantly during the first year, and these fungi were not able to prevent infections caused by the black foot disease pathogens identified as Campylocarpon spp., Dactylionectria, Ilyonectria spp., and Ilyonectria liriodendri [26].…”
Section: Introductionmentioning
confidence: 99%